Pengaruh Pemberian Edukasi Pencegahan Stunting dengan Pedoman Isi Piringku Terhadap Pengetahuan Ibu Hamil - Nissa Nur Maulidiah; Qomariyah Qomariyah; Desi Soraya (Lembaga Pengembangan Kinerja Dosen, 2025)
A continuous lack of nutritional intake causes stunting, a condition of malnutrition that leads to growth disorders in infants. Providing pregnant women with balanced nutrition education is one of the preventive measures against stunting. Objective: The research determined the effect of providing education on stunting prevention using the